The Prevalence of Clinical Depression and Its Associated Factors Among Adult Inmates in Kajang Prison, Malaysia - Yaacob, Yusadilah M. (The prison journal, 2022)
Information on clinical depression and its associated factors among prison inmates is especially scarce in countries of lower middle income. This study aims to investigate the prevalence of clinical depression and its associated factors among adult inmates in a Malaysian Prison. Clinical depression was assessed using Patient's Health Questionnaire-9 (PHQ-9). Of the total 301 inmate participants, 127 (42.2%) had clinical depression. The associated factors include male gender, violent offense, and lower social support from friends. The findings may inform early intervention to prevent clinical depression among inmates.